2006
DOI: 10.1007/11894100_5
|View full text |Cite
|
Sign up to set email alerts
|

The Essence of Dataflow Programming

Abstract: Abstract. We propose a novel, comonadic approach to dataflow (streambased) computation. This is based on the observation that both general and causal stream functions can be characterized as coKleisli arrows of comonads and on the intuition that comonads in general must be a good means to structure context-dependent computation. In particular, we develop a generic comonadic interpreter of languages for context-dependent computation and instantiate it for stream-based computation. We also discuss distributive l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 35 publications
0
30
0
Order By: Relevance
“…-functors and their fmap operations-covers any kind of labelled datastructures that support relabeling; -free completely iterative monads-non-wellfounded leaf-labelled trees with grafting and (a specific flavor of) iteration; -cofree recursive comonads-wellfounded node-labelled trees with upward accumulation and recursion; -non-empty list type-a special case of the previous item; we get effortless efficiency for comonadically structured causal dataflow computation [25].…”
Section: Other Generalizationsmentioning
confidence: 99%
“…-functors and their fmap operations-covers any kind of labelled datastructures that support relabeling; -free completely iterative monads-non-wellfounded leaf-labelled trees with grafting and (a specific flavor of) iteration; -cofree recursive comonads-wellfounded node-labelled trees with upward accumulation and recursion; -non-empty list type-a special case of the previous item; we get effortless efficiency for comonadically structured causal dataflow computation [25].…”
Section: Other Generalizationsmentioning
confidence: 99%
“…Apart from arrows, other formalisms such as monads, comonads, and applicative functors have been used to model computations over data streams (Bjesse et al, 1998;Uustalu & Vene, 2005;McBride & Paterson, 2008). Central to many of these approaches are the representation of streams and computations about them.…”
Section: Alternative Formalismsmentioning
confidence: 99%
“…However, notably missing are the connections between stream computation and the related laws. For example, Uustalu and Vene (2005) concluded that comonad is a suitable model for dataflow computation, but it lacks the discussion on comonadic laws.…”
Section: Alternative Formalismsmentioning
confidence: 99%
“…An alternative way to look at streams is modelling them as comonads [13]. However, comonads need extra machinery to be able to express applicative combinators, which come for free given the monadic interface.…”
Section: Closing Thoughtsmentioning
confidence: 99%